Altered levels of LIL3 isoforms in Arabidopsis lead to disturbed pigment–protein assembly and chlorophyll synthesis, chlorotic phenotype and impaired photosynthetic performance. (23rd April 2015) - Lohscheider, Jens N.; Rojas‐Stütz, Marc C.; Rothbart, Maxi; Andersson, Ulrica; Funck, Dietmar; Mendgen, Kurt; Grimm, Bernhard; Adamska, Iwona
Abstract Light‐harvesting complex (LHC)‐like (LIL) proteins contain two transmembrane helices of which the first bears a chlorophyll (Chl)‐binding motif. They are widespread in photosynthetic organisms, but almost nothing is known about their expression and physiological functions. We show that two LIL3 paralogues (LIL3:1 and LIL3:2) in Arabidopsis thaliana are expressed in photosynthetically active tissues and their expression is differentially influenced by light stress. Localization studies demonstrate that both isoforms are associated with subcomplexes of LHC antenna of photosystem II. Transgenic plants with reduced amounts of LIL3:1 exhibited a slightly impaired growth and have reduced Chl and carotenoid contents as compared to wild‐type plants. Ectopic overexpression of either paralogue led to a developmentally regulated switch to co‐suppression of both LIL3 isoforms, resulting in a circular chlorosis of the leaf rosettes. Chlorotic sectors show severely diminished levels of LIL3 isoforms and other proteins, and thylakoid morphology was changed. Additionally, the levels of enzymes involved in Chl biosynthesis are altered in lil3 mutant plants. Our data support a role of LIL3 paralogues in the regulation of Chl biosynthesis under light stress and under standard growth conditions as well as in a coordinated ligation of newly synthesized and/or rescued Chl molecules to their target apoproteins.